FOREIGN EXPERIENCE OF ADVOCACY AND ITS ADAPTATION TO THE DOMESTIC ADVOCATE SYSTEM (Bulletin of criminological association of Ukraine, 2024)
This article studies the experience of advocacy in leading democratic countries of the world, on the basis of which practical recommendations have been developed aimed at improving the functioning of this body in Ukraine. The features of administrative and legal regulation of advocacy in EU countries have been studied, its comparative and comparative analysis with the norms of current Ukrainian legislation regulating advocacy in the country has been conducted. The study of the world experience of advocacy in developed countries of the world is necessary and conditioned by the need to reform this body within the framework of the gradual reformatting of the Ukrainian legal field, aimed at its future synchronization with the legal ecosystem of the European Union, since the European path of development for our country is without alternative. The degree of realization of their constitutional rights by citizens depends on the effectiveness of the work of Ukrainian lawyers, and as a result, it can be stated that the activity of the advocacy is one of the main foundations of any democratic country, therefore the study is of great relevance, is important and meets the needs of the present.
Keywords: advocacy; legal practice; European Union; lawyer; legislation; legal field; reform; digitalization; artificial intelligence; legal ecosystem